2021
DOI: 10.1186/s12889-021-11159-z
|View full text |Cite
|
Sign up to set email alerts
|

Race/ethnicity differences in risk and protective factors for marijuana use among U.S. adolescents

Abstract: Background Little is known about how race and ethnicity influence marijuana-specific risk and protective factors in U.S. adolescents. We examined differences in risk and protective factors of marijuana use (MU) and their associations with MU by race/ethnicity. Methods The present study used data from the 2015–2019 National Survey on Drug Use and Health. A total of 68,263 adolescents (aged 12 to 17 years) were divided into seven subgroups by race/et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…For instance, Dai estimated that 18.4% of Hispanic middle and high school students reported cannabis vaping in 2018 compared with 14.5% of their non-Hispanic counterparts. The higher prevalence of cannabis vaping and CBD vaping among Hispanic youths compared with White youths may be associated with potential lower harm perception of cannabis use and lower media literacy . Among noncurrent e-cigarette users, this study also identified a higher prevalence of current CBD vaping among gay or lesbian and bisexual students than their heterosexual counterparts.…”
Section: Discussionmentioning
confidence: 61%
“…For instance, Dai estimated that 18.4% of Hispanic middle and high school students reported cannabis vaping in 2018 compared with 14.5% of their non-Hispanic counterparts. The higher prevalence of cannabis vaping and CBD vaping among Hispanic youths compared with White youths may be associated with potential lower harm perception of cannabis use and lower media literacy . Among noncurrent e-cigarette users, this study also identified a higher prevalence of current CBD vaping among gay or lesbian and bisexual students than their heterosexual counterparts.…”
Section: Discussionmentioning
confidence: 61%
“…In addition to considerations related to cultural issues and youths' sex differences, there is a need to inform drug use prevention interventions according to adolescents' perceptions of harm associated with drug use. This need has been emphasized by epidemiologists and public health researchers, particularly because epidemiological studies clearly indicate that perception of drug use harm is closely associated with youths' likelihood of substance use (M. H. Lee et al, 2021; Parker & Anthony, 2018). However, there is much to be learned about how such perception of risk operates among adolescents.…”
Section: The Current Investigationmentioning
confidence: 99%
“…With regard to alternatives to increase drug use harm perceptions, empirical studies indicate that parenting practices are particularly effective to influence adolescents' perceptions of harm, while also acting as protective factors for additional problematic behaviors (M. H. Lee et al, 2021; Parker & Anthony, 2018). Of interest, perception of harm can be influenced not only by addressing parent–youth communication but through alternative protective parenting practices such effective monitoring and supervision (Prado et al, 2007).…”
Section: The Current Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to their White counterparts, Black adolescents report that the consequences at school would be more severe if a student were caught smoking (Wallace & Muroff, 2002). Black adolescents also report greater perceived peer disapproval of MU than White adolescents (Lee et al, 2021). If Black youth experience greater social consequences of MU in the school setting (e.g., greater teacher or peer disapproval), MU could have more deleterious effects on school adjustment for Black youth, but the existing research on these associations are limited.…”
Section: Developmental Sequencing Of School Adjustment and Mu In Adol...mentioning
confidence: 99%